(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
The purpose of this study is to determine how much and what type of problem posing activities are included in the secondary school mathematics textbooks. In the study, secondary school mathematics textbooks of 2016-2017 academic year presented in the internet environment by the Training and Education Board were analyzed. A total of six mathematics books were analyzed in the research; two of them published by National Education Ministry and four of them published by private publishers. The books were evaluated in terms of the extent and types of problem posing activities included. As the results of the research, it was seen that there were limited number and variety of problem posing activities in all the books except the 8th grade textbook published by a private publisher. Furthermore, in the books analyzed, it was found that there was no balanced distribution of problem posing activities in the sub-learning areas and that there was not a book including all types of problem posing activities that cover all of the learning areas. Based on these results, to be able to in accordance with the purpose of the curriculum, it is suggested that secondary school mathematics textbooks should include more and diverse problem posing activities in the manner that will cover the learning areas in a balanced way. It was also found that there was no balanced distribution of problem posing activities in the lower learning areas, and no publishing house where all of the problem-setting types are used. In a similar vein, it was seen that there were no publishing houses that provided problem-setting activities for the entire learning area. In the study, textbooks were suggested to provide problem-setting activities more appropriately in accordance with the purpose of the curriculum, and to diversify problem-building activities.